The relationship of tourism and geography for the development of sports activities: a bibliometric analysis - Álvarez-Meneses, Tannia; Valderrama, Eliana Leonor; Gamba, Jorge-Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Tourism and geography have a direct relationship and the conditions of the territory can promote the development of particular tourist activities such as sports tourism. However, it is still not clear how sports tourism and the geographical aspects are configured to make visible the impacts and drivers of this type of tourism in a territory. In this sense, the objective of this study is to understand how tourism and geography are related to the development of sports activities. To fulfil the objective of this article, a bibliometric analysis was carried out using a mixed sequential quanti-quali approach. In the quantitative phase, based on a search equation, 734 records were analysed through the VOSviewer software, which made it possible to identify the knowledge map and trends of the relationship between sports tourism and geography. Likewise, the quantitative approach yielded the knowledge clusters that served as the basis for the qualitative phase, which privileged the descriptive discourse analysis strategy, where 101 documents were selected with the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses). The study produced important findings on the relationship between tourism and geography for the development of sports activities, where environmental, physical, economic and sociocultural conditions are the elements that most influence the relationship.The results allow a greater understanding of the phenomenon under study and could be taken as a starting point for the development of empirical studies in different contexts.